The History of Propeller Flaps - Hyakusoku, Hiko; Ono, Shimpei (Seminars in Plastic Surgery, 2020)
Several pedicled flaps were developed by Hyakusoku at the Nippon Medical School Hospital, Tokyo, Japan, in the 1980s to treat a large number of patients with postburn contractures. In this setting, the propeller flaps were described for the first time in 1991. The term propeller was used because of the blade shape of the skin island rotating on its axis. In 1989, Koshima introduced the term perforator flaps, whereas Hallock, in 2006, applied the perforator flap concept to the propeller flap. The name perforator pedicled propeller flap followed. Propeller flap had developed to be an important operative technique and a hot topic in the field of reconstructive microsurgery, with the important contribution of Teo. In 2009, the First Tokyo Meeting on Perforator and Propeller Flaps was held, where Pignatti reported the consensus on the definition and classification of propeller flaps that was given by the advisory panel of the meeting. Further evolutions developed since then will be described in this dedicated issue of Seminars of Plastic Surgery.
Keywords: propeller flaps; definition of propeller; history of propeller